2008
DOI: 10.1097/cad.0b013e3282f28ffb
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E analog, alpha-tocopherol ether-linked acetic acid analog, alone and in combination with celecoxib, reduces multiplicity of ultraviolet-induced skin cancers in mice

Abstract: The goals of this study were to determine whether alpha-tocopherol ether-linked acetic acid analog (alpha-TEA), a novel vitamin E analog, and celecoxib, alone or in combination, when administered as a late intervention can reduce the ultraviolet-induced nonmelanoma skin-tumor burden of established tumors, prevent additional tumors from developing, and prevent tumor recurrence once treatments are stopped. Hairless SKH-1 female mice were ultraviolet-irradiated for 24 weeks, divided into treatment groups so that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Synergetic anti-cancer effect was observed even if platinum-resistant tumor was used [83]. The developed aerosol formulation of liposomal α-TEA was successfully combined with liposomal 9-nitro-camptohecin, liposomal paclitaxel or celecoxib to reduce tumor burden as well as lung and lymph node metastases in various animal cancer models [84][85][86][87].…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Synergetic anti-cancer effect was observed even if platinum-resistant tumor was used [83]. The developed aerosol formulation of liposomal α-TEA was successfully combined with liposomal 9-nitro-camptohecin, liposomal paclitaxel or celecoxib to reduce tumor burden as well as lung and lymph node metastases in various animal cancer models [84][85][86][87].…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Photo‐chemoprevention by natural compounds ameliorates the adverse effects of UVB on the skin and considers as an alternative strategy to control the photocarcinogenesis process . Topical application of natural compounds has long been known to protect skin from oxidative damage . Moreover, due to their anti‐inflammatory properties, it can be used for the treatment of inflammation‐associated skin damage .…”
Section: Introductionmentioning
confidence: 99%
“…Interest in phytopharmaceuticals is accelerating since a growing group of studies has indicated that nutritional factors play an important role in many human diseases. Large and heterogeneous groups of botanicals, nutraceuticals and herbal drugs have been identified and evaluated during recent years, especially for their activities against cancer [1][2][3][4][5][6][7][8][9][10][11][12][13]. These agents include curcumin from turmeric, green tea polyphenols, boswellic acid from genus Boswellia, genistein from soybean, vitamin E, rosmarinic acid from rosemary and lavender, 6-shoagol from ginger rhizome and resveratrol from berries, which will be primarily introduced in this review.…”
Section: Introductionmentioning
confidence: 99%